Marulić and the Metaphysical Dimension of History - Novaković, Darko (Array, 1999)
The arguments of Marulić's Epistle to Pope Adrian VI are based on the diagnosis of Christian guilt which the author expounded in his texts at least twenty years before sending his open letter.